The effect of nitrification inhibitors and sulfur on the efficiency of nitrogen fertilizers added to calcareous soil on barley plant in El-Jabal El Akhdar region - Abdalla, Yosef H.; Majid, Ahmed A.; Abdelnaby, Omran H. (Al-Mukhtar Journal of Sciences, 2016)
A pot experiment was conducted to evaluate the effect of nitrogen fertilizer sources in relation to sulfur and nitrification inhibitors application on growth and NO3 content of barley plants (Hordeum vulgare L.) grown in a calcareous soil. Soil samples were collected from Safsaf area, El-jabal Elkhdar, Libya. Results showed that the application of potassium nitrate and urea and nitrification inhibitors (carbofuran and EDTA) in the presence of sulfur, giving further increases in dry weight of plants. Soil NO3 content was significantly reduced as a result of nitrification inhibitors and sulfur, while the best effect was on dry matter yield. Reducing of NO3 in plant or soil was observed by using carbofuran more than EDTA. Soil pH and NO3 and the population of total soil bacteria have the smallest values as a result of treatment (S2% + carbofuran +KNO3).